2001
DOI: 10.1073/pnas.101119098
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide and diet: Inclusion of dietary arachidonate and docosahexaenoate leads to increased brain levels of the corresponding N -acylethanolamines in piglets

Abstract: Endogenous ligands of cannabinoid receptors have been discovered recently and include some N -acylethanolamines (NAEs; e.g., N- arachidonoylethanolamine) and some 2-acylglycerols (e.g., sn -2-arachidonoylglycerol). Previously, we found these compounds to be active biologically when administered per os in large quantities to mice. In the present work, piglets were fed diets with and without 20:4 n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
183
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 235 publications
(195 citation statements)
references
References 55 publications
8
183
2
2
Order By: Relevance
“…17,[40][41][42] Also the fatty acid composition of dietary fat may influence endocannabinoid action. 43 For example, the presence or absence of n-3 PUFAs in the diet affects endocannabinoid levels in the brain, as shown by Berger et al 44 and Watanabe et al 45 Batetta et al 46 recently found that dietary n-3 PUFAs can reduce inflammatory markers and liver triglyceride levels, and these effects were associated with lower levels of endocannabinoid ligands in peripheral organs. Finally, there is an in vitro study showing that n-3 PUFA can reduce the levels of both anandamide and 2-AG in differentiated mouse adipocytes, whereas n-6 PUFAs (that is, arachidonic acid) were found to increase endocannabinoid levels.…”
Section: Discussionmentioning
confidence: 95%
“…17,[40][41][42] Also the fatty acid composition of dietary fat may influence endocannabinoid action. 43 For example, the presence or absence of n-3 PUFAs in the diet affects endocannabinoid levels in the brain, as shown by Berger et al 44 and Watanabe et al 45 Batetta et al 46 recently found that dietary n-3 PUFAs can reduce inflammatory markers and liver triglyceride levels, and these effects were associated with lower levels of endocannabinoid ligands in peripheral organs. Finally, there is an in vitro study showing that n-3 PUFA can reduce the levels of both anandamide and 2-AG in differentiated mouse adipocytes, whereas n-6 PUFAs (that is, arachidonic acid) were found to increase endocannabinoid levels.…”
Section: Discussionmentioning
confidence: 95%
“…In support of this idea, we detected a significant negative correlation between plasma AEA levels and circulating leptin in both healthy controls and anorexic patients. Alternatively, it is possible that changes in the micro-and macronutrient composition of the diet affected circulating AEA in our AN and/or BED patients, since it has been shown in animals that the diet can significantly and directly influence the levels of AEA, but not 2-AG (Berger et al, 2001;Matias et al, 2003). Finally, we cannot exclude that AEA elevation in our patients was a nonspecific phenomenon reflecting a compensatory adaptation to the disease state, since similar increases have been reported also in other Endocannabinoids and eating disorders P Monteleone et al psychiatric conditions such as schizophrenia (De Marchi et al, 2003;Giuffrida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain fatty acids are known to be metabolized in vivo into amides (29), and it thus seems plausible that oleic acid may be a precursor to OS. Oleic acid is abundantly present in the blood and tissues.…”
Section: Discussionmentioning
confidence: 99%